Investigation of temperature and pressure effects on thermodynamic parameters of intermetallic alloy in EXAFS. Issue 1 (1st January 2020) - Duc, Nguyen Ba
Abstract: This work advances the anharmonic correlated Einstein model to investigate how pressure and temperature affect the Debye–Waller factor and thermodynamic parameters of an intermetallic alloy. By using the anharmonic correlated Einstein model in extended X-ray absorption fine structure (EXAFS) theory, analytical expressions are derived for the effective spring constant, EXAFS cumulants, the anharmonic factor, and the thermal expansion coefficient at high temperature and pressure. The results show that both the anharmonicity of the thermal atomic vibration and the effects of pressure are essential for the thermodynamic parameters and the EXAFS Debye–Waller factor, as well as showing that the anharmonic contributions are important in the EXAFS spectrum. Numerical calculations of these thermodynamic quantities are performed for pure Cu and Ag and for CuAg72 alloy, and the results are consistent with those obtained experimentally and from other theories.